Birth outcomes, puberty onset, and obesity as long-term predictors of biological aging in young adulthood - Jáni, Martin; Zacková, Lenka; Piler, Pavel; Andrýsková, Lenka; Brázdil, Milan; Marečková, Klára (Frontiers in Nutrition, 2023)
Background: Biological aging and particularly the deviations between biological and chronological age are better predictors of health than chronological age alone. However, the predictors of accelerated biological aging are not very well understood. Methods: We have conducted a second follow-up of the Czech part of the European Longitudinal Study of Pregnancy and Childhood (ELSPAC-CZ) prenatal birth cohort in young adulthood (52% male; age 28-30; n = 262) to determine the role of birth outcomes, pubertal timing, BMI, and body fat on biological aging. Birth outcomes included birth weight, length, and gestational age at birth. Pubertal timing was determined by the presence of secondary sexual characteristics at the age of 11 and the age of first menarche in girls. Biological age was estimated using the Klemera-Doubal Method (KDM), which applies 9-biomarker algorithm including forced expiratory volume in one second (FEV1), systolic blood pressure, glycated hemoglobin, total cholesterol, C-reactive protein, creatinine, urea nitrogen, albumin, and alkaline phosphatase. Accelerated/decelerated aging was determined as the difference between biological and chronological age (BioAGE). Results: The deviations between biological and chronological age in young adulthood ranged from -2.84 to 4.39 years. Accelerated biological aging was predicted by higher BMI (in both early (R2adj=0.05) and late 20s (R2adj=0.22)), subcutaneous (R2adj=0.21) and visceral fat (R2adj=0.25), puberty onset (ηp2=0.07), birth length (R2adj=0.03), and the increase of BMI over the 5-year period between the two follow-ups in young adulthood (R2adj=0.09). Single hierarchical model revealed that shorter birth length, early puberty onset, and greater levels of visceral fat were the main predictors, together explaining 21% of variance in accelerated biological aging. Conclusions: Our findings provide comprehensive support of the Life History Theory, suggesting that early life adversity might trigger accelerated aging, which leads to earlier onset of puberty but decreasing fitness in adulthood, reflected by more visceral fat and higher BMI. Our findings also suggest that reduction of BMI in young adulthood slows down biological aging.